EFEKTIVITAS KOMPOS ECENG GONDOK DAN NPK TERHADAP PERTUMBUHAN PRODUKSI SERTA PENDAPATAN TANAMAN PAKCOY - Nurul Fadilah; Nofrianil Nofrianil; John Nefri (Universitas Nusa Bangsa, 2026)
Pakcoy plants are a type of horticulture with high economic value that has the potential to be developed. However, pakcoy cultivation is still constrained by the excessive use of inorganic fertilizers without knowing the information on use and the high price of inorganic fertilizers that have the potential to damage the structure in the soil. One alternative is the use of water hyacinth compost to increase soil fertility and reduce the use of inorganic fertilizers. This study aims to analyze the effect of the application of water hyacinth compost combined with 50% NPK on growth, production and income analysis. The research has been carried out on the practice land of the Payakumbuh State Agricultural Polytechnic in March-April 2026. The research method used a one-factor Group Random Design (RAK) with 4 levels, P0 (100% NPK), P1 (water hyacinth compost 5 tons/ha + NPK 50%), P2 (water hyacinth compost 10 tons/ha + NPK 50%) and P3 (water hyacinth compost 15 tons/ha + NPK 50%) with many replicates 6. The analysis data used ANOVA and continued with the DMRT test of 5%. The results of the study showed that the level of treatment of water hyacinth compost of 10 tons/ha + 50% NPK showed the highest yield on the growth and production of pakcoy plants and produced the highest amount of income.